Analysis of gag proteins from mouse mammary tumor virus. - Hizi, A (1989)
Structural proteins designated p10gag, p21gag, p8gag, p3gag, p27gag, and p14gag from the C3H strain of mouse mammary tumor virus (MMTV) were purified by reversed-phase high-pressure liquid chromatography. The N- and C-terminal amino acid sequences and amino acid composition of each protein were determined and compared with the amino acids encoded by the proviral DNA sequences for the MMTV gag gene. The results show that each of the purified proteins is a proteolytic cleavage product derived from the predicted primary translational product of the gag gene (Pr77gag) and that their order in Pr77gag is p10-pp21-p8-p3-n-p27-p14 (where n represents 17 predicted residues that were not identified among the purified proteins). Purified p10gag lacks the initiator methionine and has a myristoyl group attached in amide linkage to the N-terminal glycine residue predicted by the second codon of the gag gene. The cleavage products are contiguous in the sequence of Pr77gag, and the C-terminal residue of p14gag is encoded by the last codon of the gag gene. By analogy with other retrovirus, p14gag is the viral nucleocapsid protein, p10gag is the matrix protein, and p27gag is the capsid protein of mature MMTV. Proteolytic cleavage sites in MMTV Pr77gag bear a striking resemblance to cleavage sites in the gag precursors of D-type retroviruses, suggesting that these viral proteases have similar specificities.